2010
DOI: 10.1128/jb.01659-09
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence ofStreptococcus gallolyticus: Insights into Its Adaptation to the Bovine Rumen and Its Ability To Cause Endocarditis

Abstract: Streptococcus gallolyticus (formerly known as Streptococcus bovis biotype I) is an increasing cause of endocarditis among streptococci and frequently associated with colon cancer. S. gallolyticus is part of the rumen flora but also a cause of disease in ruminants as well as in birds. Here we report the complete nucleotide sequence of strain UCN34, responsible for endocarditis in a patient also suffering from colon cancer. Analysis of the 2,239 proteins encoded by its 2,350-kb-long genome revealed unique featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
132
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 68 publications
(61 reference statements)
8
132
0
Order By: Relevance
“…We found 2,192 protein-coding genes on the chromosome, 192 of which were identified as potential pseudogenes, indicating an ongoing genome decay process. This hypothesis is also supported by the fact that the S. macedonicus genome is approximately 220 kb smaller than the S. gallolyticus genome (7,9,12), despite the high level of gene synteny between the two species. Such a reductive evolutionary process is common among lactic acid bacteria adapted to the food environment (10) and in the case of S. thermophilus was also accompanied by the loss of pathogenicity traits (3).…”
supporting
confidence: 50%
“…We found 2,192 protein-coding genes on the chromosome, 192 of which were identified as potential pseudogenes, indicating an ongoing genome decay process. This hypothesis is also supported by the fact that the S. macedonicus genome is approximately 220 kb smaller than the S. gallolyticus genome (7,9,12), despite the high level of gene synteny between the two species. Such a reductive evolutionary process is common among lactic acid bacteria adapted to the food environment (10) and in the case of S. thermophilus was also accompanied by the loss of pathogenicity traits (3).…”
supporting
confidence: 50%
“…Tannin tolerance has been described for the genus ) acacia condensed tannin, levels 10-fold greater than those tolerated by S. bovis (O'Donovan & Brooker, 2001). Similarly, Rusniok et al (2010) described the ability of this species to adapt to the presence of tannins in the rumen, due to its capacity to use a broad range of carbohydrates, as found in the present study (Table 1), especially those present in the plant cell wall, and to express several hydrolytic enzymes, including tannases and other phenolic compounds decarboxylases that should contribute to the detoxification of the digestive tract. Nelson et al (1997) also observed that Streptococcus was able to tolerate tannin.…”
Section: Resultsmentioning
confidence: 99%
“…AP012053.1), and ATCC BAA-2069 (accession no. FR824043) were compared by using the EDGAR software to identify genes they have in common (20)(21)(22)(23). From the resulting gene pool, a set of 22 housekeeping genes were selected on the basis of the variability and length (Ͼ500 bp) of DNA sequences or usage in other MLST schemes.…”
Section: Methodsmentioning
confidence: 99%